(untitled) (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
In the present work, nanoparticles of pure Bi2Te3 and Ag doped Bi2Te3 have been prepared using hydrothermal technique. The thermoelectric performance of bismuth telluride has been found to be improving with Ag doping. This may be due to increase in the carrier concentration resulting in enhanced electrical conductivity of the material, and expected to maintain its low thermal conductivity. The morphology, structural properties of the nanoparticles synthesized in this study has been accessed through the utilization of scanning electron microscopy (SEM) and X-ray diffraction (XRD) technique. Thin films of as prepared powders of pure Bi2Te3 and Ag doped Bi2Te3 nanoparticles have deposited on to glass substrate using thermal evaporation technique. The thermoelectric measurements of as synthesized materials have studied using an indigenously developed setup. Seebeck coefficient for pure and Ag doped bismuth telluride thin films has found to be 150 µv°C-1 and 182 µv°C-1, respectively.